(untitled) (Web of Teachers: Inderscience Research, 2024)
Nowadays, an economist with a high level of education must have mathematical knowledge. Because many issues of economics are directly related to the linear algebra course of mathematics. In this regard, the section on the system of linear equations is especially important. In this article, a mathematical model of economic problems resulting in a number of linear equations has been developed.